Assistance in the Legalization of Gawah Daya Coffee UMKM Products, Kayangan District, North Lombok Regency - Sari, Ni Kadek Wahyuni Merta; Khairunnisah, Noni Antika; Anam, Ahmad Gautsul; Mahfuz, Muhammad; Pranata, Andi (Abdi Masyarakat, 2024)
Assistance with the legalization of MSME products such as Gawah Daya Coffee is a crucial step in ensuring business continuity and legal compliance. Through a structured approach, MSMEs can meet legal requirements, increase market access and strengthen their business position. The results of the assistance show a significant increase in legal compliance, strengthening the capacity of MSME owners, and access to wider markets. With guaranteed legality, Gawah Daya Coffee MSMEs can gain long-term benefits in the form of sustainable business growth and improved image in the eyes of consumers. Assistance with the legalization of MSME products has had a significant positive impact on the growth and sustainability of MSME businesses in the coffee sector.